Literature-based database to inform policy making on marine plastic pollution in ASEAN+3 - Lim, Cheng Ling; Lyons, Youna; Liu, Yulu; Neo, Mei Lin; Müller, Moritz; Wong, Changi; Cordova, Muhammad Reza; Sulistiowati, Sulistiowati; Abreo, Neil Angelo S.; Ko Gyi, Thanda; Onda, Deo Florence; Baculi, Ronan; et al. (Frontiers in Ocean Sustainability, 2024)
The ASEAN+3 countries urgently need to present actual data on the state of their marine plastics pollution, so that they can respond to the criticisms of being the top-5 global sources of marine plastics based on modelled predictions, as well as to develop effective response policies based on sound data. While the research outputs on marine plastic pollution have increased spectacularly across these countries, their overall resource capacity to access the data remains lacking. This study describes a robust framework developed to use >700 peer-reviewed research publications from the region that can inform policy-making. First, detailed metadata fields were developed for this database focused on extracting information from the publications that are relevant to regional policy questions being asked to adequately respond to the threats posed by marine plastics. Second, the curation of research publications in this database greatly depended on a team of regional researchers, who were apt in the subject matter and a native language speaker. The latter was critical in the capture of non-English articles to boost the quality of database. Some of the key findings from the broad analyses included the rapid increase in research efforts on marine plastics between 2014 and 2021, which coincided with the growing concerns of this environmental crisis, the dominant publication language was English despite the diversity of countries, and the dominant research topic appeared to be of policy response measures. Overall, the database produced adequate and immediate data, where policy-makers can leverage for urgent actions. For example, the output on the status of marine plastic pollution is everincreasing, but the region could start to focus on knowledge gaps (e.g., sampling in critical sensitive habitats like seagrasses and coral reefs). Finally, this study presented a comprehensive summary of the current state of marine plastic pollution and knowledge gaps (e.g., technical capacity and equipment) of the region that can facilitate discussions among target audience including the governments as well as international and regional 52 regulating bodies, the research community and plastic waste management professionals.